2002
DOI: 10.1080/10871200290089355
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Fish Harvesting Decisions by Anglers

Abstract: This paper examined whether angling catch behaviors, angler characteristics, and angler evaluations could explain the decisions by anglers to harvest caught fish. Particularly, we determined if the propensity of tourist anglers to harvest caught walleye (Stizostedion vitreum), northern pike (Esox lucius), and smallmouth bass (Micropterus Dolomieui) was related to variables that measured catch rates, angling effort, catch rates for substitute fish species, motivational item importance, and/or social group varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…We considered the size structure and catch rates of catchable fish for five species, but there are many other factors that could help elucidate patterns in the self-imposed length limits. Perhaps most importantly, the harvest orientation of the different angler groups (Fisher, 1997;Aas and Vittersø, 2000;Hunt et al, 2002;Dorow et al, 2010) was not considered in this study. Anglers seeking a specific species or trophy-sized fish could have an influence on the sizes that are harvested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We considered the size structure and catch rates of catchable fish for five species, but there are many other factors that could help elucidate patterns in the self-imposed length limits. Perhaps most importantly, the harvest orientation of the different angler groups (Fisher, 1997;Aas and Vittersø, 2000;Hunt et al, 2002;Dorow et al, 2010) was not considered in this study. Anglers seeking a specific species or trophy-sized fish could have an influence on the sizes that are harvested.…”
Section: Discussionmentioning
confidence: 99%
“…Weithman and Anderson (1978) developed the minimum length for the qualitylength category from the relationship between world-record length and fish quality, and related the minimum to a length that is 36-41% of the species-specific world-record length. Even though fish harvest is an important part of the fishing experience for most anglers (Matlock et al, 1988;Peyton and Gigliotti, 1989;Spencer, 1989), the actualized minimum length of a quality-length fish likely differs between catch-and-release-orientated anglers and harvestorientated anglers (Wilde and Ditton, 1994;Arlinghaus, 2006b;Anderson et al, 2007) The decision to harvest any given fish depends on the dynamic relationship of an anglers' expectation, or perceptions, of what can be potentially caught in the waterbody within the confines of the harvest regulation (Cook et al, 2001;Hunt et al, 2002;Anderson et al, 2007). In our study, we were unable to conclude that the restriction of the harvest regulation altered the self-imposed length limits across the species assessed.…”
Section: Species 2010 2011mentioning
confidence: 99%
See 2 more Smart Citations
“…About one-fourth of the Minnesota resident anglers who targeted Northern Pike reported releasing all of the legal Northern Pike they caught while angling, whereas only about 10% of dark house spearing participants reported releasing all legal Northern Pike when angling (Schroeder and Moeckel 2011). Previous studies have reported that anglers may be less oriented toward keeping fish of lesspreferred species (Hunt et al 2002;Sutton 2003;Schroeder and Fulton 2013). Northern Pike may be a less-preferred species for many Minnesota anglers but a more-preferred species among individuals who participate in dark house spearing.…”
Section: Discussionmentioning
confidence: 93%